The Effect of Fe Concentration on the Quality and Quantity of Biogas Produced From Fermentation of Palm Oil Mill Effluent - Irvan Matseh (International Journal of Science and Engineering, 2012)
The purpose of this research is to study the effect of Fe concentration as a trace metal on the quality and quantity of biogas produced from the fermentation of palm oil mill effluent (POME). Raw POME as feed was obtained from one of the palm oil mills belong to PTPN IV, other materials used were hydrochloric acid, sodium bicarbonate, and trace metals. Observed variables were volume of biogas, concentration of Fe in raw POME and biodigester, degradation rate of total solid (TS) and volatile solid (VS), M-Alkalinity, pH, H2S and CO2 concentration in biogas at hydraulic retention time (HRT) 6 days. Before HRT of 6 days reached, initial trace metal compositions were 25.2 mg/L of Fe, 0.42 mg/L of Co, and 0.49 mg/L of Ni. After that, composition of trace metal were consisted only Co and Ni. The results showed that Fe as a trace metal did not affect the production or quantity of biogas. When Fe concentration reached over to 330 mg/L then concentration of CH4, total solid (TS) and volatile solid (VS) decreased. Moreover, the higher the Fe contents the smaller of H2S production. Fe content in POME from the same mill had different concentration, as the consequence biogas with different H2S concentrations were produced as well. Thus, Fe in the trace metals is no longer required if high concentration of Fe already existed in POME because it can reduce the formation of H2S. In addition, too high concentration of Fe in POME can be toxic for microorganism in the fermentation of biogas.